Comparison of Preoperative and Postoperative Corneal Astigmatism After Phacoemulsification Through A 2.75mm Clear Corneal Temporal Incision - Talat, Kainaat; Munawar, Tariq; Bano, Shehar; Balkees Malik, Najma; Fahad Ikram; Babar, Zaheer uddin (Pakistan Armed Forces Medical Journal, 2024)
Objective: To compare corneal astigmatism pre and post-operatively after Phacoemulsification through a 2.75mm Clear Corneal Temporal Incision. Study Design: Quasi-Experimental study. Place and Duration of Study: Combined Military Hospital, Kharian Pakistan, from January to May 2023. Patients and Methods: The data of 46 patients of age more than 55 years of either gender with cataract was collected after taking consent. Those patients were excluded from the study with past ocular history of conditions affecting corneal astigmatism. Intra-ocular lens (IOL) with previously determined power was placed following phacoemulsification through 2.75mm temporal incision. Corneal astigmatism was noted pre-operatively, and at 7th and 28th day after surgery and the differences if any were recorded subsequently. Results: Out of 46 patients, 27(58.7%) were females while 19(41.3%) were males aged 61.19+10.66 years on average. Overall variation in astigmatism in the operated patients from pre-op value to 7 and 28 days post op was 0.08+0.42D (p=0.529) and 0.14+0.48D (p=0.351). 95% of patients had a variation of <1.00 D in corneal astigmatism after surgery while >1.00 D variation was found in only 5%. Conclusion: Surgically induced astigmatism is much reduced in patients post-operatively who have undergone phacoemulsification using a temporal clear corneal incision with a 2.75mm keratome.